Extracellular vesicles released by human retinal pigment epithelium mediate increased polarised secretion of drusen proteins in response to AMD stressors. Issue 13 (8th November 2021) - Flores‐Bellver, Miguel; Mighty, Jason; Aparicio‐Domingo, Silvia; Li, Kang V.; Shi, Cui; Zhou, Jing; Cobb, Hannah; McGrath, Patrick; Michelis, German; Lenhart, Patricia; Bilousova, Ganna; Heissel, Søren; et al.
Abstract: Age‐related macular degeneration (AMD) is a leading cause of blindness worldwide. Drusen are key contributors to the etiology of AMD and the ability to modulate drusen biogenesis could lead to therapeutic strategies to slow or halt AMD progression. The mechanisms underlying drusen biogenesis, however, remain mostly unknown. Here we demonstrate that under homeostatic conditions extracellular vesicles (EVs) secreted by retinal pigment epithelium (RPE) cells are enriched in proteins associated with mechanisms involved in AMD pathophysiology, including oxidative stress, immune response, inflammation, complement system and drusen composition. Furthermore, we provide first evidence that drusen‐associated proteins are released as cargo of extracellular vesicles secreted by RPE cells in a polarised apical:basal mode. Notably, drusen‐associated proteins exhibited distinctive directional secretion modes in homeostatic conditions and, differential modulation of this directional secretion in response to AMD stressors. These observations underpin the existence of a finely‐tuned mechanism regulating directional apical:basal sorting and secretion of drusen‐associated proteins via EVs, and its modulation in response to mechanisms involved in AMD pathophysiology. Collectively, our results strongly support an active role of RPE‐derived EVs as a key source of drusen proteins and important contributors to drusen development and growth.